2019
DOI: 10.1590/1981-6723.05418
|View full text |Cite
|
Sign up to set email alerts
|

Atividade biológica e quantificação de compostos bioativos em extrato de erva-mate e sua aplicação em hambúrguer de peixe

Abstract: Resumo A erva-mate possui compostos biologicamente ativos com aplicação industrial. Cafeína, rutina e ácido clorogênico presentes neste produto possuem atividade antioxidante e o último ainda é antimicrobiano. Este estudo objetivou avaliar a atividade biológica do extrato de erva-mate e quantificar compostos bioativos, bem como aplicar o extrato em hambúrguer de peixe para determinar seu poder conservante. A atividade antioxidante foi avaliada por DPPH (2,2-difenil-1-picrihidrazila) e FRAP (poder de redução do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
1
17
0
4
Order By: Relevance
“…The proximate composition results are shown in table 3. Similar moisture values were found by TONET et al (2019), in Nile tilapia hamburgers with manioc flour and MELO et al (2014) for Tilapia CMS hamburger, with variation in relation to proteins, ashes and lipids. COSTA et al (2019), in the production of fishburgers published similar results with this research for lipids and high protein content.…”
Section: ----------Independent Variables-----------------------------supporting
confidence: 85%
“…The proximate composition results are shown in table 3. Similar moisture values were found by TONET et al (2019), in Nile tilapia hamburgers with manioc flour and MELO et al (2014) for Tilapia CMS hamburger, with variation in relation to proteins, ashes and lipids. COSTA et al (2019), in the production of fishburgers published similar results with this research for lipids and high protein content.…”
Section: ----------Independent Variables-----------------------------supporting
confidence: 85%
“…Fish fillets evaluated, after submersion in yerba-mate extract, stored for 12 months at 7 ºC, also showed few changes, due to the antioxidant action of the compounds 51 . Fish burgers added with yerba-mate extract showed a preservative action due to the presence of quantified phenolics 18 .…”
Section: New Food Products With Yerba-mate Extractmentioning
confidence: 99%
“…The use of yerba-mate extracts in the development of new products with technological potential has been highlighted 17 , both in the food and pharmaceutical industries. Research developed over the years has sought to turn common foods into functional foods by adding yerba-mate extracts [18][19][20][21][22][23][24] . Studies have shown that the inclusion of yerba-mate in the diet improves the immune system, reduces oxidative stress, improves cholesterol and triglycerides [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em outros artigos, os extratos Aquoso e hidroalcoólico de I. paraguariensis demonstraram possuir melhor atividade antimicrobiana frente a E. coli spp. (COSTA et al, 2017;AFONSO et al,2017;TONET et al, 2019;SILVA et al, 2016;BURRIS et al, 2012;). Já em dois estudos onde foram analisados extratos diclorometano, metanólico e etanólico, não houve atividade antibacteriana registrada nas concentrações testadas frente a E. coli spp, o que demonstra que este tipo de extrato pode possuir substâncias não ativas frente a este patógeno (CARELLI et al, 2013;MARTIN et al, 2013).…”
Section: Atividade Antimicrobianaunclassified